2006
DOI: 10.1111/j.1600-6143.2006.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pancreas Transplantation in the United States Using Cardiac-Death Donors

Abstract: Recipients of a SPK transplants from DCD and DBD donors had equivalent patient and graft survival rates at 1, 3 and 5 years. For recipients of SPK transplants, the wait for organs from DCD donors was significantly shorter than that for organs from DBD donors. SPK recipients of organs from DCD donors had longer hospital stays than did recipients of organs from DBD donors. With renal allografts, the incidence of delayed graft function was almost four times higher with organs from DCD donors than with organs from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 29 publications
2
61
2
1
Order By: Relevance
“…In addition, planned recipients of both DCD and DBD organs were admitted before the donor went to theatre (DBD) or had treatment withdrawn (DCD). In this study, cold ischaemia times in the DBD group were thus substantially lower than those reported elsewhere 14 , although this policy did, on several occasions, result in the recipient not receiving a transplant because the organs were unsuitable on inspection or, for DCD donors, asystole did not occur within 4 h after treatment withdrawal.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In addition, planned recipients of both DCD and DBD organs were admitted before the donor went to theatre (DBD) or had treatment withdrawn (DCD). In this study, cold ischaemia times in the DBD group were thus substantially lower than those reported elsewhere 14 , although this policy did, on several occasions, result in the recipient not receiving a transplant because the organs were unsuitable on inspection or, for DCD donors, asystole did not occur within 4 h after treatment withdrawal.…”
Section: Discussioncontrasting
confidence: 63%
“…The largest report is from an United Network of Organ Sharing registry analysis of 47 DCD SPK transplants that showed equivalent graft survival rates at 1, 3 and 5 years for organs from DCD and DBD donors 14 . Single-centre long-term follow-up has shown no difference in patient and graft survival at 8 years 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence reported in the literature ranges from 1% to 40% and accounts for 29% of grafts lost within the first 6 months after transplantation 3, 4. Reported risk factors for PAT include donor age, body mass index (BMI), atherosclerosis, donation after circulatory death (DCD), death from cerebrovascular accident, and premortem severe hypotension 5, 6. Recipient risk factors include vascular disease, thrombophilic state, history of previous thrombotic events, and hypotension in the intraoperative or postoperative period 3.…”
Section: Introductionmentioning
confidence: 99%
“…At the other extreme, several studies have shown reduced long-term pancreas graft survival with pancreata from donors older than 50 years of age [21,22]. Although fewer than 5% of all pancreas transplants are obtained from donors after cardiac death, there are recent reports of excellent longterm graft survival with pancreata from donors after cardiac death, comparable to that of pancreata from brain dead donors [23,24]. However, the incidence of delayed kidney graft function was significantly higher in recipients of organs from donors after cardiac death in these studies.…”
Section: Discussionmentioning
confidence: 99%